Design of Supporting Material Warehouse Management System at PT XYZ - Rahardjo, Benedictus; Surya, Danielle (International Journal of Industrial Research and Applied Engineering, 2017)
This study has been done to create a system and standard to control the warehouse and also make it easier to find tools. The warehouse is full and finding tools is difficult because there is no regulation to control how the warehouse works. This research uses direct observation in the field, and interviews with the department related to supporting tool warehouses. The results of the observations is the organization of a new management system in the form of Standard Operating Procedure (SOP), rules, and a new layout for tools. Based on the existing SOP, stock cards and material, a  parent table is made for controlling tools in the warehouse. Controlling is carried out with aim that the warehouse works according to its SOP and eliminates current problems.